Antropologi a scuola? Strategie abilitanti per saperi di confine - Laura Faranda (EtnoAntropologia, 2014)
The paper presents a reflection on the opportunity of guiding anthropology students to achieve the educational credits required for school teaching qualification. The author provides an overview of this option by encouraging young anthropologists to think about school as a possible job opportunity, as well as a metaphor of ethnographic fieldwork and an effective anthropological training.